Standard specification for Wrought Alloy Steel Rolls for Cold and Hot Reduction (American Society of Testing Materials, 2008)
This specification covers homogeneous wrought hardened alloy steel rolls for use in cold or hot reduction of flat rolled ferrous and nonferrous products.